Fracture initiation and propagation in soft hydraulic fracturing of hot dry rock - Xiaoxia ZHOU; Gensheng LI; Zhengchao MA; Zhongwei HUANG; Xu ZHANG; Shouceng TIAN; Wenchao ZOU; Tianyu WANG (Petroleum Exploration and Development)
By considering the thermo poroelastic effects of rock, the constitutive relationship of fatigue deterioration of rock under cyclic loading, elastic-brittle failure criteria and wellbore stress superposition effects, a thermal-hydraulic-mechanical- fatigue damage coupled model for fracture propagation during soft hydraulic fracturing in hot dry rock (HDR) was established and validated. Based on this model, numerical simulations were conducted to investigate the fracture initiation and propagation characteristics in HDR under the combined effects of different temperatures and cyclic loading. The results are obtained in three aspects. First, cyclic injection, fluid infiltration, pore pressure accumulation, and rock strength deterioration collectively induce fatigue damage of rocks during soft hydraulic fracturing. Second, the fracture propagation pattern of soft hydraulic fracturing in HDR is jointly controlled by temperature difference and cyclic loading. A larger temperature difference generates stronger thermal stress, facilitating the formation of complex fracture networks. As cyclic loading decreases, the influence range of thermal stress expands. When the cyclic loading is 90%pb and 80%pb (where pb is the breakdown pressure during conventional hydraulic fracturing), the stimulated reservoir area increases by 88.33% and 120%, respectively, compared to conventional hydraulic fracturing (with an injection temperature of 25 °C). Third, as cyclic loading is further reduced, the reservoir stimulation efficiency diminishes. When the cyclic loading decreases to 70%pb, the fluid pressure far away from the wellbore cannot reach the minimum breakdown pressure of the rock, resulting in no macroscopic hydraulic fractures.